APAKAH PERILAKU DAN ASUPAN MAKAN BERLEBIH BERKAITAN DENGAN STRESS PADA MAHASISWA GIZI YANG MENYUSUN SKRIPSI?[Whether There is A Correlation Between Behavior and Excess Food Intake with the Stress in Nutrition Student Who Preparing for the Undergraduate Thesis?] - Zuhairoh Naily Syarofi; Lailatul Muniroh (Media Gizi Indonesia, 2020)
College students have a high suceptibility to experience stress, especially those in last semester who write thesis. If stress not managed correctly, students could experienced negative behaviour like emotional over eating that could infl uence nutritional status. Those problems even occur in nutrition students who already had proper knowledge of health and nutrition practices. This research aims to analyze correlation between emotional over eating behaviour and intake with stress leves and scors of perceived stress scale among nutrition students who write thesis. This research was an observational analytic using cross sectional design. Subjects were 34 nutrition students taken by simple random sampling. Data were collected by perceived stress scale, eating appraisal due to emotion and stress (EADES), questionnaire, and 2 x 24hour food recall. Data were analyzed using Pearson and Spearman Correlation. Results showed correlation between stress level with emotional eating (p=0.008, r=-0.448), scores of perceived stress scale with energy intake (p=0.028, r=0.376), and fat intake (p=0.002, r=0.507). Conclusion of this study is high stress level can be a trigger for emotional eating as a coping strategy that leads to over intake in nutrition students who write thesis. Since food choice could be a problem when having stress, emotional eating can be balanced by perfomed a right food choice as daily intake needs.